Compliance and Visual Outcome Of “Treat-And-Extend” Versus “Pro Re Nata”Dosing of Intravitreal Bevacizumab in Wet Age-Related Macular Degeneration – A Perspective From a Developing Country - Joshi, Kriti; KC, Anadi Khatri; Rijal, Roshija Khanal; Rai, Salma KC; Lammichane, Gyanendra; Yadav, Roshan Dev (Birat Journal of Health Sciences, 2020)
Introduction: Age- related Macular Degeneration (AMD) is the commonest cause of irreversible blindness and visual impairment in elderly, aged50 years or older contributing 8.7% of global blindness. Among the two types: “dry” and “wet”, the “wet” variant is treated using anti-VEGFs, mainly via two regimen – PRN or TREX.Objective: To study and compare the compliance, cost and visual outcome of “Treat-and- Extend (TREX)”versus “Pro Re Nata(PRN)” dosing of intravitrealbevacizumab in Wet AMD.Methodology: Sixty-four eyes of 64 patients with treatment naïve neovascular AMD were included and randomly divided into two groups, with each group comprising 32 eyes, by lottery system: “Group A [TREX]” and “Group B [PRN]”. Group A was treated with intravitrealbevacizumab [1.25mg/0.05ml] at presentation and at 1-month interval for 3 consecutive months [loading dose] and monthly till dry macula was obtained. Group B was treated with the same in “as needed” basis.Both Groups were followed up, for 1 year.Results Mean gain in visual acuity in the PRN group was 0.09 +/- 0.35 log MAR unit and in TREX, it was 0.14 +/- 0.3 log MAR unit within the period of 1 year.64% of the patients were compliant in TREX and 36% moderately complaint whereas in the PRN group, 24% were compliant, 60% moderately compliant and 16% noncompliant. Average hospital cost in PRN and TREX was NRs. 16, 170 (USD 149) and 23,785(USD 220) respectively.Conclusion: Compliance and visual outcome were better in TREX in comparison toPRN at 1 year of treatment with intravitrealbevacizumab for Wet AMD.